Shiloh - Levitt, Zane W.; Rosenbloom, Dale.; Moriarty, Michael, 1941-; Heron, Blake; Wilson, Scott, 1942-; Dowd, Ann.; Wright, J. Madison; Roth, Shira; Wright, Tori.; Bartlett, Bonnie; Steiger, Rod, 1925-2002.; Byers, Frank; et al. ([United States] : Warner Home Video, 2001)
When he finds a lost beagle in the hills behind his West Virginia home, Marty tries to hide it from his family and the dog's real owner, a mean-spirited man known to shoot deer out of season and to mistreat his dogs.
Originally produced as a motion picture in 1996.
Based on the novel by Phyllis Reynolds Naylor.
Special features: Behind-the-scenes footage; Roger Ebert review; theatrical trailer.
Director of photography, Frank Byers ; editor, Mark Westmore ; music, Joel Goldsmith.
Michael Moriarty, Blake Heron, Scott Wilson, Ann Dowd, J. Madison Wright, Shira Roth, Tori Wright, Bonnie Bartlett, Rod Steiger.
MPAA rating: PG.
Keywords: Dogs -- Drama; Animal welfare -- Drama; West Virginia -- Drama; Feature films